Ficus microcarpa L., F. benjamina L. and other species introduced in the New World, their pollinators (Agaonidae) and other tig wasps - Ramírez B., William (Revista de Biología Tropical, 1988)
The invasion of the Old World fig F. mieroearpa L. (section Conosycea) in U.S.A., Mexico and Central America by its Old World pollinator Parapristina verticillata is reported. Because of the size of the seedlings growing naturally in Florida, Honduras, and the State of Morelos, Mexico, and the fact that no seedlings were found in other parts of Mexico and El Salvador, we postulate that P. verticillata probably arrived to those areas within the last five years. It is probable that P. verticillata will move south invading all the tropical and subtropical countries where F. microcarpa is abundantly planted. Walkerella, a nonpollinating wasp was also found in Brazil and Florida inhabiting the syconia of F. microcarpa. The syconia of Old World F. benjamina L. (section Conosycea) in Costa Rica, were found pollinated by the New World Pegoscapus tristani. The pollinator of F. padifolia H.B.K. (section Americana). The syconia of Old World F. religiosa L. (section Urostigma) in Miami, Florida, were found to be pollinated by the symbiotic agaonid of the native F. aurea Nutt. Hybrid seedings were found growing naturally. Species of Ficus which evolved in different geographic areas, such as islands or continents could also evolve equally or similarly attracting synomones, which can confuse foreing agaonids and other sycophilous wasps when a species of fig is introduced.